Peran Polres Mimika dalam Penyelesaian Konflik Antar Suku Damal Melalui Pendekatan Perspektif Hukum - Andyka Aer (CV. Syntax Corporation Indonesia, 2021)
Tribal conflict (war) in the Land of Papua apparently becomes a part of life that will be difficult to leave for the community. Tribal war not only happened between among others tribes but also inside the tribes itself, Damal Tribal War for example. In the process of the conflict resolution, it involves many stakeholders included the Police. The Police involvement in handling tribal war in Papua has a strategic role to complete it as well as possible. As the law enforcement officer, police acts based on the applicable national legal provisions. However, if it is applied on the people of Papua, there will be gap hence the strategic effort is needed in resolving it in order to actualize the sustainable security. This research is using descriptive-qualitative analysis, which the data is collected through observation, interview, and documentation study, particularly related to the roles of Mimika Police (Polres Mimika) in conflict resolution among Damal Tribes through law perspective approach. The result of this research shows that the conflict among the Damal Tribes is caused by many things such as offense, breach of agreement, liquor, woman, etc. Then, Mimika Police in handling the war tribes takes a socio-cultural approach to the parties in conflict hence they can resolve the conflict that occurs. Besides that, Mimika Police does not only enforce the national law on tribal wars in Papua but also takes consideration from the customary law that apply in community.